1987
DOI: 10.1029/jd092id08p09693
|View full text |Cite
|
Sign up to set email alerts
|

Physical modeling and analysis of rain and clouds by anisotropic scaling multiplicative processes

Abstract: We argue that the basic properties of rain and cloud fields (particularly their scaling and intermittency) are best understood in terms of coupled (anisotropic and scaling) cascade processes. We show how such cascades provide a framework not only for theoretically and empirically investigating these fields, but also for constructing physically based stochastic models. This physical basis is provided by cascade scaling and intermittency, which is of broadly the same sort as that specified by the dynamical (nonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
864
0
8

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,006 publications
(879 citation statements)
references
References 28 publications
7
864
0
8
Order By: Relevance
“…The emphasis is on the physical picture and diagrams, rather than on mathematics and equations. There is a large literature on other atmospheric aspects, particularly in the rainfall and hydrological literature stemming from the publication of Schertzer and Lovejoy (1987). Surface temperature (Koscielny-Bunde et al, 1998;Syroka and Toumi, 2001) has been examined, as has ozone column density Varotsos, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The emphasis is on the physical picture and diagrams, rather than on mathematics and equations. There is a large literature on other atmospheric aspects, particularly in the rainfall and hydrological literature stemming from the publication of Schertzer and Lovejoy (1987). Surface temperature (Koscielny-Bunde et al, 1998;Syroka and Toumi, 2001) has been examined, as has ozone column density Varotsos, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The multiscaling framework has been successfully employed to provide a theoretical basis for the empirically observed scale-dependent behavior of flood peaks in the context of regional quantile analysis [e.g., Gupta and Waymire, 1990;Gupta et al, 1994;Gupta and Dawdy, 1995]. Other applications of this concept have appeared in atmospheric turbulence, rain and clouds (e.g., see Schertzer and Lovejoy [1987] for an early reference), in river networks [e.g., Gupta and Waymire, 1989], and in solute transport [Sposito and Jury, 1988]. In this paper, it is shown that the multiscaling framework can provide a theoretical basis for interpreting and modeling the scale and frequency dependent relations between channel morphometry and discharge (known as HG).…”
Section: Introductionmentioning
confidence: 99%
“…over a large range of wavenumber k. The spectral exponent b contains information about the degree of stationarity of the data [5,6]. If b < 1, the field is stationary; if 1 < b < 3, the field contains nonstationary signal with stationary increments and in particular, the small-scale gradient field is stationary; if b > 3, the field is nonstationary with nonstationary increments.…”
Section: Stationaritymentioning
confidence: 99%